The Effect of Androgynus Sauropus Feeding on Breast Milk Adequacy in Postpartum Mothers in Village C, Purwakarta Regency in 2024 - Nurfitri, Tia; Prawitasari, Yeni (CV. Publikasi Indonesia, 2025)
Breast milk is essential for infant health, yet many postpartum mothers face challenges in milk production. This study examines the effect of Sauropus androgynus (katuk leaves) on breast milk adequacy among postpartum mothers in Village C, Purwakarta Regency, Indonesia, in 2024. Using a quasi-experimental design with a one-group pretest-posttest approach, 36 respondents were assessed before and after consuming katuk leaves. Results showed that 58.3% of mothers experienced increased milk production post-intervention, with the highest improvement observed in multipara mothers (69.5%) and those aged 20–35 years (58.3%). Additionally, 80.5% of mothers breastfeeding more than eight times daily reported abundant milk. The Wilcoxon test confirmed the intervention's significance (p = 0.000 < 0.05). Findings align with prior research highlighting katuk leaves' efficacy due to their alkaloids, sterols, and nutrient content. The study concludes that regular consumption of katuk leaves enhances milk production, supporting its use as a natural lactation aid. Implications include promoting katuk leaves in maternal health programs to improve breastfeeding rates and infant nutrition.